Moisture sensitivity alteration of soil organic carbon and nitrogen mineralization in Vertisol - SARKAR, ABHIJIT; BISWAS, ASHIS KUMAR; GHOSH, AVIJIT; JHA, PRAMOD; DAS, MADHUMITA; PATRA, ASHOK KUMAR; ROY, TRISHA; SAHA, MADHUMONTI; PATRA, ASHOK KUMAR; ROY, TRISHA; SAHA, MADHUMONTI; BISWAS, SIDDHARTHA SANKAR; et al. (The Indian Journal of Agricultural Sciences, 2021)
Uneven distribution and intensity of rainfall in subtropical semi-arid Vertisol creates different hydro-climaticcondition due to its mineralogy and expansive type of clays. Indeed, information on impact of moisture levels onsoil C- and N-mineralization in presence of residue and recommended fertilization is scarce. Thus, this incubationexperiment was conducted at ICAR-Indian Institute of Soil Science, Bhopal during 2018â€“19 with four moisture, twofertilizer, and two residue levels to evaluate the effects of fertilization and residue incorporation on moisture sensitivityof soil C- and N-mineralization. Application of fertilizer induced positive priming effect for CO2-C and increased by~ 28%. Residue- and fertilizer Ã— residue accelerated the Ccum by ~108 and 125%, respectively. Residue applicationcaused initial N-immobilization. A significant interaction was observed among fertilizer, residue and moisture contentfor both C- and N-mineralization. C-mineralization was amplified with increase in soil moisture content from 24to 40% moisture levels, but decreased at 48% moisture level. Irrespective of fertilization moisture sensitivity of Cand N mineralization was reduced by residue incorporation. But, fertilization led to highest moisture sensitivity ofN-mineralization. Thus, residue incorporation could be recommended as obligatory practice in sub-tropical Vertisolto decrease its moisture sensitivity and to maintain positive C balance and soil health.